ENHANCING COMMUNICATION SKILLS OF PROSPECTIVE TEACHERS THROUGH THERU-K-KOOTHU (STREET PLAY) – AN EMPIRICAL RESEARCH STUDY - Parthiban, V.; Vakkil, M. (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Communication skills are the ability of a person that helps him to perform effectively in the workplace. These skills include active listening, speaking, observing, and empathizing which improve an employee's relationship and performance on the job. Particularly in the teaching profession, communication skills are a prerequisite for teachers. The teachers who have good communication skills perform meritoriously in their institution. Also, the organizations are expecting teacher candidates with good communication skills for recruitment. It is the need of the hour to improve the communication skills of the trainee teachers. Therefore, the researchers intended to find out the effectiveness of theru-k-koothu (street play) to enhance the communication skills, specifically the public speaking skills of prospective teachers. An experimental research method was adopted for the study and 32 prospective teachers were selected as samples. The results of the study indicated that the maximum number of prospective teachers have a moderate level of public speaking skills. Also, it is found that the Theru-k-Koothu (street play) training program is more effective in developing the public speaking skills of prospective teachers. The findings of the study provide insights for the educationists and policymakers to integrate communication skills efficiently in the teacher education program to make quality and proficient teachers.